Breast cancer cutaneous metastases mimicking Papilloma Cutis Lymphostatica. Biopsy to avoid pitfalls. (2018) - Giudice, Giuseppe; Vestita, Michelangelo; Robusto, Fabio; Annoscia, Paolo; Ciancio, Francesco; Nacchiero, Eleonora
Highlights: We present a singular case of secondary lymphedema is the most frequent long-term complication of axillary lymphadenectomy. It can result in complication as erysipelas, warts, Papilloma Cutis Lymphostatica (PCL), or angiosarcomas. Moreover, in women affected by breast cancer an accurate differential diagnosis among these conditions or complication related to radiation dermatitis or cutaneous metastasis is essential. We report the case of a 60-year-old postmenopausal Caucasian woman affected by secondary lymphedema following complete mastectomy for breast cancer. These lesions had clinical typical features of PCL, but histopathological analysis revealed dermo-hypodermic metastasis of breast carcinoma. The presence of skin lesions in secondary lymphedema after oncological lymphadenectomy requires an accurate differential diagnosis. In fact, these lesions can emulate degenerative or infective skin diseases; anyway, in patients affected by secondary lymphedema other less common conditions - as PLC, nodular-type lichen myxedematosus or Gottron's carcinoid papillomatosis - should be taken into account. Our case reports the possibility that metastases of breast cancer might also mimic these conditions. Abstract: Introduction: Secondary lymphedema is the most frequent long-term complication of axillary lymphadenectomy. It can result in complication as erysipelas, warts, Papilloma Cutis Lymphostatica (PCL), or angiosarcomas. Moreover, in women affected by breast cancer an accurate differential diagnosis among these conditions or complication related to radiation dermatitis or cutaneous metastasis is essential. Presentation of case: We report the case of a 60-year-old postmenopausal Caucasian woman affected by secondary lymphedema following complete mastectomy for breast cancer. The patient after surgery was treated with radiotherapy, chemotherapy and hormone therapy, developing a lympedema of left arm after few months. These lesions had clinical typical features of PCL, but histopathological analysis revealed dermo-hypodermic metastasis of breast carcinoma. Discussion: The presence of skin lesions in secondary lymphedema after oncological lymphadenectomy requires an accurate differential diagnosis. In fact, these lesions can emulate degenerative or infective skin diseases; anyway, in patients affected by secondary lymphedema other less common conditions – as PLC, nodular-type lichen myxedematosus or Gottron's carcinoid papillomatosis – should be taken into account. Conclusion: Our case reports the possibility that metastases of breast cancer might also mimic these conditions.